Boron-doped diamond electrode modified by polytetrafluoroethylene to enhance the degradation of atrazine - DING Jia; LI Yu; GUAN Baohong (浙江大学学报. 农业与生命科学版)
Atrazine (ATZ) is one of the most popular herbicides, and the pollution of atrazine to surface water and groundwater has aroused people’s concern, which is urgent to research and develop water purification technology to deal with it. Boron-doped diamond (BDD) electrode has the advantage of highly efficient production of ·OH, but the degradation of organic pollutant is seriously limited because the ·OH is trapped on the surface of the electrode. In this study, BDD electrode modified by polytetrafluoroethylene (PTFE) improved the degradation efficiency of ATZ. In NaCl solution, after modification with 5.0%, 8.6% and 20.0% PTFE dispersions, the quasi-first order kinetic constants of ATZ degradation reaction were improved by 98.9%, 88.2% and 78.6%, respectively. In NaHCO3 and Na2SO4 solutions, after modification with 8.6% PTFE dispersion, the quasi-first order kinetic constants of ATZ degradation reaction were improved by 49.2% and 127.0%. The PTFE was coated on the surface of BDD electrode in the form of film, which was beneficial to the improvement of the current. Meanwhile, the bubbles that adhered to the surface of BDD were conducive to the formation of ·OH and diffusion of ·OH into the homogeneous solution. The concentration of ·OH in the solution bulk increased by 17.73, 19.89 and 18.81 times after the modification of 5.0%, 8.6% and 20.0 % PTFEs, respectively, and the degradation efficiency of ATZ and removal effect were significantly enhanced. The main ways of ATZ degradation by PTFE modified BDD electrode were dealkylation, dechlorination-hydroxylation and alkyl oxidation reactions.